Analisis Pengaruh Penerapan Green Accounting, Kinerja Lingkungan Dan Pengungkapan Corporate Social Responsibility Terhadap Return Saham - Sekar Arum Nurlatifah; Annafi Indra Tama (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2024)
Abstract This study aims to provide information for investors and company managers in understanding the factors that influence stock returns. It also highlights the importance of sustainability strategies in increasing investment attractiveness. In the capital market, PT Unilever Indonesia Tbk faced a 30.95% year-to-date decline in share price. To deal with this situation, the company took strategic initiatives by prioritizing ecosystem preservation efforts. This step is expected to improve investor interest and optimize stock returns. This study aims to investigate the impact of green accounting, environmental performance and corporate social responsibility disclosure on stock returns. This research methodology uses classical assumption tests and unbalanced data regression analysis using the help of E-Views 12 software. The type of data used is secondary data obtained from non-cyclical consumer sector companies listed on the Indonesia Stock Exchange. The sample was selected using purposive sampling technique covering the period 2020-2022, resulting in 31 sample companies as research subjects. The findings of this study found that the application of green accounting and environmental performance has an influence on stock returns. while the disclosure of corporate social responsibility has no influence on stock returns. Keywords: green accounting; environmental performance; csr; stocks return.